2013
DOI: 10.1590/s0100-83582013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Density and sowing season of two Brachiaria species on the soybean culture

Abstract: -The aim of this study was to evaluate the growth and yield of soybean cultivar M-8766 in consortium with Brachiaria brizantha. BRS Piata and Brachiaria ruziziensis at different densities and sowing dates. The experimental design was randomized blocks with treatments arranged in a factorial 2 x 2 x 3 with four replications. Used as factors grass species (Brachiaria brizantha Piata and Brachiaria ruziziensis BRS) intercropped with soybean M-8766, sowing dates (12 and 24 days after soybean emergence) and three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(11 reference statements)
0
6
0
2
Order By: Relevance
“…BRS Piatã e U. ruziziensis, quando semeadas na densidade de 10 kg ha -1 , aos 24 dias após a emergência da soja, reduziram a produtividade desta cultura de forma distinta, com decréscimos de 3,03 e 16,23%, respectivamente (Saraiva et al, 2013). Diversos autores relatam U. brizantha e B. pilosa como plantas daninhas de grande importância para diversas culturas (Biffe et al, 2010;Pinotti et al, 2010;Camargo et al, 2011;Pereira et al, 2012), inclusive para soja (Oliveira et al, 2013).…”
Section: Introductionunclassified
“…BRS Piatã e U. ruziziensis, quando semeadas na densidade de 10 kg ha -1 , aos 24 dias após a emergência da soja, reduziram a produtividade desta cultura de forma distinta, com decréscimos de 3,03 e 16,23%, respectivamente (Saraiva et al, 2013). Diversos autores relatam U. brizantha e B. pilosa como plantas daninhas de grande importância para diversas culturas (Biffe et al, 2010;Pinotti et al, 2010;Camargo et al, 2011;Pereira et al, 2012), inclusive para soja (Oliveira et al, 2013).…”
Section: Introductionunclassified
“…Numerical but not significant differences were observed for this variable, similarly to what was reported in other studies with soybean intercropped with forages of the genus Urochloa spp. (Pereira et al, 2011;Mariani et al, 2012;Saraiva et al, 2013;Franchini et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies on intercropping focus on the possibility of competition between forages and soybean, there are no reports on changes in the grain yield components of the oilseed when intercropped with grasses (Mariani et al, 2012;Saraiva et al, 2013;Crusciol et al, 2014;Franchini et al, 2014). Significant differences, however, were found by Crusciol et al (2012) and Saraiva et al (2014), who observed reduction in the number of pods per plant and of grains per pod in the soybean + U. brizantha intercropping.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, deve-se utilizar meios de se evitar os efeitos negativos da convivência entre a forrageira e a cultura de interesse principalmente durante o período crítico de prevenção de interferência (PCPI). De acordo com Saraiva et al (2013), B. ruziziensis semeada nas densidades de 5 a 10 kg ha -1 aos 12 e 24 dias após a emergência (DAE) da soja 'M-8766 RR', não causou redução na produtividade da cultura. Segundo Silva et al (2004), foi necessário aplicar 54 g ha -1 de fluazifop-p-butil sobre B. brizantha, aos 21 DAE da soja 'UFV-16' em consórcio, para obter produtividade semelhante ao da testemunha.…”
Section: Resultsunclassified